Effect Of Water Clover (Marsilea Crenata) Leaf Extract On Estrogen Receptors-Β In Skin Aging - winawati eka putri wina; maria ulfa maria (Jurnal Ilmiah Kesehatan, 2021)
Extrinsic and intrinsic factors influence skin aging. Hormonal changes, especially estrogen, significantly affect intrinsic skin aging. Decreased circulating estrogen levels reduce skin collagen content and skin elasticity. Isoflavones in Marsilea crenata (MC) leaf are active substances containing compounds that mimic estrogen. This study aims to analyze MC leaf extract against the estrogen receptor (ER)-β. The sample for this research was female Wistar Rats (Rattus norwegicus). All of them were 12 months old, with their weight was between 350 to 550 grams divided into five groups. P1 P2 and P3 were grouping with MC leaf extract administration in sequential doses 20 mg/kg BW, 30 mg/kg BW, and 40 mg/kg BW. At the same time, P4 was a positive control group, and P5 was a negative control group. The independent variable was M.crenata leaf extract. The dependent variables were (ER)-β expression and dermal thickness. The data analysis utilized the one-way analysis of variance (ANOVA) showed significant differences (p< 0.05). Each group showed significant results, and group P2 showed the highest expression of (ER)-β and dermal thickness. The result showed that there were significant correlations between both variables (P<0.05). This research has proved that water clover extract could become an alternative treatment in the future for skin aging. However, further research should find a proper dose for human consumption.